Miniaturized HOXB13 Mimetics Are Sequence-Specific, Methyl-Sensitive DNA Binders - Claire Wong; Shiao Y. Chow (Journal of the American Chemical Society, 2026)
Abstract Homeobox protein Hox-B13 (HOXB13) is an oncogenic transcription factor that is associated with prostate cancer risk. Unlike most transcription factors (TFs), HOXB13 is a methyl-plus TF and has been shown to be preferentially recruited to DNA prostate cancer risk loci. Here, we miniaturized HOXB13 to create metal-stapled mimetics that can target its cognate primary DNA-binding site in a sequence-specific, methyl-sensitive manner. Targeted profiling of 5-methylcytosine (5mC) recognition using V269X mimetic mutants revealed that leucine can further enhance both methyl sensitivity and methyl specificity through methyl–methyl contact with 5mC and decreased methyl–pi interactions with cytosine. Collectively, our study revealed novel insights into the molecular interactions of HOXB13 with methylated DNA and new tools that will provide a structural basis for future development of a new class of sequence-specific methylated DNA binders.